Social and psychological mechanisms of functioning the image of a modern leader in the conditions of the modern stage of development of the Ukrainian society - Turуnіna O.; Ilyanova, A. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2018)
The work is devoted to the psychological analysis of the features of the image of the leader at the present stage of development of the Ukrainian state. The need for psychological studies of the image is conditioned by the contradictions between the social practice of image functioning in different spheres of social life and the need for its theoretical reflection. Methods based on the means of social and psychological influence become significant. Among these tools, the image of the leader is essential. During the creation of his vision, the leader demonstrates the most attractive individual, personal, and professional qualities, learns to see them in themselves "from the side", is aware of his shortcomings, correlates his own characteristics with the standard of personality. In recent years, the concept of the image has firmly entered the information space. In most cases, the image is perceived by people like a specific value, which is associated with the success of certain activities, both individual and collective. Representatives of psychological science have increased their interest in the phenomenon of an image, as evidenced by the sharp increase in recent years in the number of scientific publications on topics related to the image or its aspects. As a result of research using the methods of a questionnaire survey followed by in-depth interviews in focus groups, the ranking structure of the expert model of an ideal modern leader and the ranking structure of the image model of a modern leader in everyday consciousness are presented. The findings of the study described the socio-psychological mechanisms of the functioning of the image as a phenomenon of interpersonal interaction, including: the manifestation of the characteristics of group interaction; the use of social representations and stereotypes; the realization of the self-concept of the subject of the image in correlation relationships with the self-concepts of other subjects of image interaction and the like. The disclosure of the socio-psychological mechanisms of the functioning of the image, their accounting and use are necessary for the development of productive activities on the formation of an optimal image as a phenomenon of interpersonal interaction.